Implementasi PHBS menggosok gigi berbasis Tri-N pada siswa kelas III SDN Kwagon Sleman - Angelina Nazalina Haryono; Poppy Indriyanti (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
This study aims to implement the Tamansiswa "Tri N" teachings on the importance of brushing teeth at Kwagon Public Elementary School. Observations and research results show that students are able to implement healthy living by brushing their teeth properly. Students are taught by teachers about the importance of maintaining oral hygiene through tooth brushing. This study is a qualitative descriptive study that describes the implementation of "Tri N" through tooth brushing activities in Grade III students of Kwagon Public Elementary School. Data collection techniques used were observation techniques and direct demonstration practices. This socialization and practice of proper tooth brushing went smoothly thanks to the students' extraordinary ability and enthusiasm. This was evident during the tooth brushing practice at Kwagon Public Elementary School.